2021
DOI: 10.3390/ijms22031107
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Accumulation Strongly Allied with Genetic Male Sterility Convertible to Cytoplasmic Male Sterility in Kenaf

Abstract: Male sterility (MS) plays a key role in the hybrid breed production of plants. Researchers have focused on the association between genetic male sterility (GMS) and cytoplasmic male sterility (CMS) in kenaf. In this study, P9BS (a natural GMS mutant of the kenaf line P9B) and male plants of P9B were used as parents in multiple backcross generations to produce P9SA, a CMS line with stable sterility, to explore the molecular mechanisms of the association between GMS and CMS. The anthers of the maintainer (P9B), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…2020). Plant organellar genomes encode proteins necessary for the electron transport chains of respiration and photosynthesis and disruption of these pathways can result in the excess production of DNA damaging reactive oxygen species (ROS; Liu et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2020). Plant organellar genomes encode proteins necessary for the electron transport chains of respiration and photosynthesis and disruption of these pathways can result in the excess production of DNA damaging reactive oxygen species (ROS; Liu et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Increased recombination between short repeat sequences may disrupt genes, organellar genome stoichiometry, and genome organellar replication, which is recombination-dependent in plants ( Shedge et al 2007 ; Rowan et al 2010 ; Chevigny et al 2020 ). Plant organellar genomes encode proteins necessary for the electron transport chains of respiration and photosynthesis and disruption of these pathways can result in the excess production of DNA damaging reactive oxygen species (ROS; Liu et al 2021 ). Although a direct link between ROS-mediated damage to DNA and mutation rates remains contentious ( Kennedy et al 2013 ; Itsara et al 2014 ; Broz et al 2021 ; Waneka et al 2021 ; Sanchez-Contreras et al 2021 ), ROS molecules have been shown to indirectly affect point mutation rates by impairing proofreading capabilities via damage to the metazoan mtDNA polymerase (Pol γ; Anderson et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of excess ROS in wheat was associated with abnormal PCD progression in the tapetal layer [43]. An abnormal accumulation of ROS was also found in kenaf CMS line P9SA [44]. MDA is a common indicator of peroxidation related to oxidative stress, and usually high MDA can cause cell damage through nucleic acid reaction with proteins, lipids, and organelles [45].…”
Section: Abnormal Ros and Antioxidant Defense System Leading To Tapet...mentioning
confidence: 99%
“…Furthermore, ATP and NADH depletion can block ascorbic acid -glutathione cycle in mitochondria, inducing mitochondrial dysfunction and expression of mitochondrial chimeric open reading frame (Ling Huang, 2011). In cotton, CMS-D8 line Zhong 41A (Yang et al, 2018a), Kenaf CMS line H722A (Zhou et al, 2019) and P9SA (Liu et al, 2021), suppression of ROS elimination ability led to rapid release of ROS and abnormal microspore development.…”
Section: Introductionmentioning
confidence: 99%